Evaluation of the antibacterial and wound healing efficacy of Aloe vera-coated 3-0 silk sutures in comparison to uncoated 3-0 silk sutures following flap surgery - A randomized clinical trial - Dipika Mitra; Rhea Vivek Kashid; Gaurav Prabhakar Shetty; Shruti Prasanna Patil; Rohit Ajay Shah (Journal of Indian Society of Periodontology)
Background: The efficacy of surgical interventions relies on appropriate closure of the surgical site, which should also be devoid of bacteria. Plaque accumulation is a constant challenge that hampers the healing outcome. Sutures used to close the wound serve as reservoirs for microbes, increasing the risk of surgical site infections (SSIs). To avoid this, sutures can be coated with antimicrobial agents such as Aloe vera, which could be delivered to the healing site. To the best of our knowledge, there is no reported literature on using Aloe vera-coated sutures for the closure of wounds following flap surgery. Materials and Methods: It was a split-mouth, randomized clinical trial, in which 24 sites requiring conventional flap surgery were selected, of which 12 were assigned to Group A (uncoated sutures) and 12 to Group B (Aloe vera-coated sutures). On the 8th day, sutures were sent for microbiological analysis to count the colony-forming units (CFUs). The Early Healing Score (EHS) and Visual Analog Scale (VAS) Scores were recorded. Results: The intergroup comparison of VAS scores, EHSs, and CFUs between Group 1 and Group 2 was done using the Whitney U-test. It showed statistically significant differences between the two groups for the EHS and CFUs, but not for VAS scores. Thus, Group 2 shows better results as compared to Group 1. Conclusion: Based on the results, it was interpreted that the use of microbicidal sutures coated with Aloe vera demonstrates microbicidal properties and aids in preventing SSIs.